Ibn Fadlanâ€™s Role in The Islamisation of Bulghar Society - Halim, Harliana; Yusoff, Kamaruzaman; Ahmad, Shakila; Faizal Abdul Khir, Mohd; Hafiz Abdullah, Abdul; Suraya Aziz, Hani; Sholeh Saad, Shamsaadal; Sulaim, Abdullah (International Journal of Engineering and Technology, 2018)
Islam is the oldest established religion among Bulghar entity, the residents along the riverbanks of the Volga-Kama triangle. This valley was famous as the first Islamic country erected in the Eastern European region. The presence of Islam in the region has raised the name of the ruler of Volga Bulgaria and was reinforced by relationship with Baghdad. The Islamisation of the Bulghar society is relevant to the role played by Ahmad ibn Fadlan, the ambassador of the Abbasid government based in Baghdad. Therefore, this article aims to examine the role played by Ibn Fadlan in the Islamization of the Bulghar society. For this study, a qualitative method using historical descriptive approach was employed, which involved compilation and evaluation of the facts of the Risalah Ibn FadlÄn. Data for this study were obtained through library research. The data analyses were conducted through texts and document analyses, as well as comparison method. This study finds that Ibn Fadlan plays an important role in the islamisation of the Bulghar society, not just as an ambassador of Abbasid government but as a teacher, preacher and counselor to the Bulghar king and the whole nation.Â Â
Keywords: Ibn Fadlan; Bulghar Society; Islamisation